Feasibility of subcutaneous implantable cardioverter‐defibrillator implantation with opioid sparing truncal plane blocks and deep sedation. (22nd October 2018) - Miller, Marc A.; Garg, Jalaj; Salter, Benjamin; Brouwer, Thomas F.; Mittnacht, Alex J.; Montgomery, Morgan L.; Honikman, Rafael; Arkonac, Derya E.; Choudry, Subbarao; Dukkipati, Srinivas R.; Reddy, Vivek Y.; Weiner, Menachem M.
Abstract: Introduction: The subcutaneous implantable cardioverter‐defibrillator (S‐ICD) is most commonly implanted under general anesthesia (GA), due to the intraoperative discomfort associated with tunneling and dissection. Postoperative pain can be substantial and is often managed with opioids. There is a growing interest in transitioning away from the routine use of GA during S‐ICD implantation, while also controlling perioperative discomfort without the use of narcotics. As such, we assessed the feasibility of a multimodal analgesia regimen that included regional anesthesia techniques in patients undergoing S‐ICD implantation. Methods and Results: Twenty patients received truncal plane block (TBL) immediately before S‐ICD implantation. The first 10 patients were implanted under general anesthesia (GA + TBL), and the next 10 patients were implanted under deep sedation (DS + TBL). Additionally, the DS + TBL patients were also prescribed a structured regimen of nonopioid analgesics in the perioperative period. Opioid consumption was calculated as milligram morphine equivalents (MME). In‐hospital opioid consumption was significantly lower in the patients implanted with DS + TBL (MME = 0) as compared with patients receiving GA + TBL (MME = 60; P = 0.004). Conclusions: Subcutaneous ICD implantation with anesthesia‐delivered DS and a multimodal anesthetic regimen that includes TBL is feasible and associated with significantly less perioperative opioid consumption. Abstract : The subcutaneous implantable cardioverter‐defibrillator (S‐ICD) is most commonly implanted under general anesthesia (GA) due to the intraoperative discomfort associated with tunneling and dissection. Postoperative pain can be substantial, and is often managed with opioids.